“That Sottish and Selfish principle”: Cugoano on Self-Interest, Imagination, and Moral Wrongdoing - Aminah Hasan-Birdwell (Journal of Modern Philosophy)
The following paper analyzes Ottobah Cugoano’s argument against the type of moral wrongdoing of those who participated in the practices of the transatlantic slave trade and of enslavement. I will argue that Cugoano describes moral wrongdoing in a general and particular sense. In a general sense, Cugoano depicts a form of moral wrongdoing or behavior that applies to humanity as a whole and is essentially a state of selfishness in which reason is superseded by a “viciated imagination.” Selfishness is equated with drunkenness or stupidity. The imagination is erroneously used to invent reasons and justifications for one’s actions outside of concern for others. Cugoano describes the particular sense of wrongdoing that follows from his general observations, especially when he analyzes the specific practices of the traders, kidnappers, and enslavers in the transatlantic slave trade. These practices represent something exemplary because they demonstrate collective and coordinated efforts of moral wrongdoing. Cugoano describes the enslavers as a self-interested group of men outside of the bounds of civil society since they are not guided by “any human law or divine, except the rules of their own fraternity.” The paper will conclude by focusing on the philosophical and ethical dimensions of Cugoano’s descriptions of imagination and moral wrongdoing.